2020
DOI: 10.1111/psyp.13636
|View full text |Cite
|
Sign up to set email alerts
|

Cross system autonomic balance and regulation: Associations with depression and anxiety symptoms

Abstract: The autonomic nervous system (ANS) has demonstrated utility for identifying alterations in emotion processing associated with common psychopathology, including depression and anxiety. To date though the majority of this ANS research has several limitations. Most studies have examined parasympathetic and sympathetic branches separately, requiring activity in the other branch be inferred. This is problematic as each branch may function independently. Composite indices such as cardiac autonomic balance (CAB) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 79 publications
4
46
1
Order By: Relevance
“…Autonomic nervous system imbalance, or an increase in sympathetic activity coupled with a decrease in parasympathetic activity, has been associated with poorer physiological health outcomes including metabolic abnormalities (Licht et al, 2013) and cardiovascular disease risk factors (i.e., hypertension, diabetes) (Thayer et al, 2010b), as well as worse psychological outcomes, including anxiety (Friedman and Thayer, 1998), depression (Stone et al, 2020), and increased levels of daily stress (Mitchell et al, 2017). Due to its importance in health research, there have been several attempts to accurately measure cardiac autonomic balance and regulation over the years using various physiological measures.…”
Section: Autonomic Balance and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic nervous system imbalance, or an increase in sympathetic activity coupled with a decrease in parasympathetic activity, has been associated with poorer physiological health outcomes including metabolic abnormalities (Licht et al, 2013) and cardiovascular disease risk factors (i.e., hypertension, diabetes) (Thayer et al, 2010b), as well as worse psychological outcomes, including anxiety (Friedman and Thayer, 1998), depression (Stone et al, 2020), and increased levels of daily stress (Mitchell et al, 2017). Due to its importance in health research, there have been several attempts to accurately measure cardiac autonomic balance and regulation over the years using various physiological measures.…”
Section: Autonomic Balance and Healthmentioning
confidence: 99%
“…CAB and CAR can be calculated using indices of parasympathetically mediated HRV (e.g., the root mean square of successive differences [RMSSD], HF-HRV) and impedance derived systolic time intervals (i.e., pre-ejection period [PEP]) as an index of sympathetic activity (Berntson et al, 2008;Williams et al, 2017). Both CAB and CAR have been used as indices of autonomic balance and activity in a myriad of studies, showing associations with affective responses (Kreibig et al, 2012), psychopathologies (Bylsma et al, 2015;Stone et al, 2020), stress (Gump et al, 2011;Mitchell et al, 2017), inflammatory markers (Singh et al, 2009;Alen et al, 2020), and physiological health (Berntson et al, 2008;Vrijkotte et al, 2015). For example, a history of myocardial infarctions and type 2 diabetes diagnoses are more likely to be linked to low levels of CAR and CAB, respectively (Berntson et al, 2008), while lower CAB has also been shown to be associated with increased levels of inflammatory cytokines such as interleukin-6 and tumor necrosis factor alpha (Alen et al, 2020).…”
Section: Autonomic Balance and Healthmentioning
confidence: 99%
“…Typically, researchers interested in sympathetic activity assess either skin conductance (electrodermal activity, EDA), or PEP, as both are assumed to be relatively “pure” indices of sympathetic activity. However, recent work reveals that these indices may not even be significantly correlated (Stone et al., 2020) and may show differential relationships with parasympathetic activity and emotion regulation processes (Stone et al., 2020). This could be due to differences in temporal resolution in PEP and electrodermal measures (i.e., as electrodermal measures tend to have a slower onset and offset), or the fact that PEP is primarily driven by beta‐adrenergic neurotransmission, while electrodermal measures reflect primarily cholinergic neurotransmission (Stone et al., 2020; Stone et al., 2020).…”
Section: Characterization Of Within and Cross‐level Interactions Acromentioning
confidence: 99%
“…However, recent work reveals that these indices may not even be significantly correlated (Stone et al., 2020) and may show differential relationships with parasympathetic activity and emotion regulation processes (Stone et al., 2020). This could be due to differences in temporal resolution in PEP and electrodermal measures (i.e., as electrodermal measures tend to have a slower onset and offset), or the fact that PEP is primarily driven by beta‐adrenergic neurotransmission, while electrodermal measures reflect primarily cholinergic neurotransmission (Stone et al., 2020; Stone et al., 2020). Further, skin conductance reactivity has been more associated with threat of punishment, while PEP reactivity is more sensitive to reward receipt or anticipation (Obradović & Boyce, 2012), suggesting that the nature of the stimuli and context may be particularly relevant.…”
Section: Characterization Of Within and Cross‐level Interactions Acromentioning
confidence: 99%
“…To our knowledge, this study was the first to investigate the negative emotional bias in MDD from the aspect of internal-external information integration by interoception. With converging evidence reporting the intimate connections between the peripheral nervous system and emotion in MDD ( 55 , 56 ), the role of allostasis in depression pathological mechanism could not be ignored anymore. In the current study, we found that abnormal HEPs could predict aberrant LPP clusters in sad face trials only in the MDD group, indicating the possibility that aberrant interoception dysfunction has led to abnormal processing of sad faces in MDDs.…”
Section: Discussionmentioning
confidence: 99%